Equilibrium distributions and the nanostructure diagram for epitaxial quantum dots - Rudd, R; Briggs, G; Sutton, A; Medeiros-Ribeiro, G; Williams, R (2007)
We present in detail a thermodynamic equilibrium model for the growth of nanostructures on semiconductor substrates in heteroepitaxy and its application to germanium deposition on silicon. Some results of this model have been published previously, but the details of the formulation of the model are given here for the first time. The model allows the computation of the shape and size distributions of the surface nanostructures, as well as other properties of the system. We discuss the results of the model, and their incorporation into a nanostructure diagram that summarizes the relative stability of domes and pyramids in the bimodal size distributions. Copyright © 2007 American Scientific Publishers. All rights reserved.